Does Africa really benefit from trade? - Matthias Busse; José Luis Groizard (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
We empirically analyse the impact of trade on income levels in the sub-Saharan African countries. The results indicate that the linkage between these two variables is negative for these countries. This outcome may explain the negative sign of the Africa dummy in income (or growth) regressions.
Keywords: F1; O24; O40; 330; Trade; Income Levels; Sub-Saharan Africa